STUDI PERKEMBANGAN PRESTASI ATLET PPLP TENIS MEJA JAWA TENGAH TAHUN 2008-2013 - Dwi Pramesianto, Andriya; Waluyo, Waluyo (Jurnal Phederal Penjas, 2014)
The objectives of  research to determine: (1) Leadership organization of PPLP Table Tennis Central Java (2) The coaching of Achievement of PPLP Table Tennis Central Java (3) infrastructure and facilities available in PPLP Table Tennis Central Java (4) The method of training conducted by PPLP Table Tennis Central Java (5) The achievement ever achieved by PPLP Table Tennis Central Java (6) Regenerasi Table Tennis athletes of PPLP Central Java (7) Sources of funding / sponsorship of PPLP Table Tennis Central Java (8) Academic achievement of table Tennis athlete of PPLP Central Java (9) After being an athlete of PPLP table Tennis Central Java.This research used descriptive qualitative method. The subject of this research is PPLP Table Tennis Central Java. Techniques of data collection used documents techniques, observation  and direct interview to the administrators, coaches and athletes. Technique of analyzing data used analysis model which includes the components (1) Data collection (2) data reduction (3) Data Servings (4) The withdrawal of conclusion.Based on the results obtained the following conclusions: (1) Table Tennis Organization PPLP Central Java is good, because in this  organization has been equipped with elements that support the running of the organization and the division of work is good. (2) The coaching of achievement that  conducted by PPLP Table Tennis Central Java is good, because the coaching that is conducted through the stages of coaching that include elements pemassalan, regenerasi and talent guiding. (3) Infrastructure and facilities owned by PPLP Table Tennis Central Java is good, because it can support the activities that conducted in advancing coaching the athlete's achievement. (4) training program conducted by PPLP Table Tennis Central Java is good enough, because of the absence training periodization in dealing with the championship, only  the daily program of  exercise that includes basic technique exercise and physical exercise. (5) Achievement was achieved  by PPLP Table Tennis Central Java at the national level is good, it can be seen from every championships which held in the National level. (6) regenerasi athletes that conducted by PPLP Table Tennis Central Java is good. By monitoring the way in the games and doing surveys in the clubs then can determine the quality of  athletes that will be coached in PPLP directly, so they can assess whether the athlete can perform more appropriate with what is expected. (7) The source of funding of athletes PPLP table tennis Central Java is derived from the ABPN Ministry, so that the prosperity of athletes are covered by the country. (8) Table Tennis PPLP Central Java not only considers on  table tennis achievement , but also consider on  the academic achievement. Academic achievement of athletes PPLP Table Tennis Central Java is good, it is seen in the reports of student learning result  that always get scores above the average, almost the same with other students in school. (9) Some of athletes graduated from PPLP Table TennisCentral Java  continue the study in university and also have a work. They get a good university and a good company in Indonesia.